Elective Surgery but not Transjugular Intrahepatic Portosystemic Shunt Precipitates Acute‐On‐Chronic Liver Failure. Issue 7 (26th March 2021) - Chang, Johannes; Bamarni, Avend; Böhling, Nina; Zhou, Xin; Klein, Leah‐Marie; Meinke, Jonathan; Duerr, Georg Daniel; Lingohr, Philipp; Wehner, Sven; Brol, Maximilian J.; Rockstroh, Jürgen K.; Kalff, Jörg C.; et al.
Abstract : Acute‐on‐chronic liver failure (ACLF) is a syndrome associated with organ failure and high short‐term mortality. Presence of ACLF at interventions, such as surgery or transjugular intrahepatic portosystemic shunt (TIPS), has been shown to determine outcome, but those interventions have also been attributed to precipitate ACLF in different studies. However, dedicated investigation for the risk of ACLF development in these interventions, especially in elective settings, has not been conducted. Patients with cirrhosis undergoing elective surgery were propensity score matched and compared to patients receiving TIPS. The primary endpoint was ACLF development within 28 days after the respective procedure. The secondary endpoint was 3‐month and 1‐year mortality. In total, 190 patients were included. Within 28 days, ACLF developed in 24% of the surgery and 3% of the TIPS cohorts, with the highest ACLF incidence between 3 and 8 days. By day 28 after the procedure, ACLF improved in the TIPS cohort. In both cohorts, patients developing ACLF within 28 days after surgery or TIPS placement showed significantly worse survival than patients without ACLF development at follow‐up. After 12 months, mortality was significantly higher in the surgery cohort compared to the TIPS cohort (40% vs. 23%, respectively; P  = 0.031). Regression analysis showed a European Foundation Chronic Liver Failure Consortium acute decompensation (CLIF‐C AD) score ≥50 and surgical procedure as independent predictors of ACLF development. CLIF‐C AD score ≥50, C‐reactive protein, and ACLF development within 28 days independently predicted 1‐year mortality. Conclusion: Elective surgical interventions in patients with cirrhosis precipitate ACLF development and ultimately death, but TIPS plays a negligible role in the development of ACLF. Elective surgery in patients with CLIF‐C AD ≥50 should be avoided, while the window of opportunity would be CLIF‐C AD <50. Abstract : image